What causes supply levels from African livestock sectors to change? - McClintock, J. (International Livestock Centre for Africa, 1983)
Examines changes in supply levels of livestock products, viz, in Africa from 1965 to 1980. Also examines easily available aggregate data on livestock output and factors that may affect it to discover why some countries in sub-saharan Africa have performed appreciably better than others in terms of increasing their supply of livestock products. Covers seven products, viz, beef, sheep and goat meat, poultry meat, all meat, cow milk and all milk.